DEVELOPMENT OF AN OPTIMUM SOLAR POWER TOWER MODEL USING EVACUATED TUBE RECEIVER - SAID ALI, BASIL HASSAN (2018)
Evacuated tubes, tracking and concentrating solar power technologies have strengthen the competitiveness of solar energy in the fields of power generation and heat for industries.